Impact of Abusive Clauses on a Level of Legal Risk - Wiśniewski , Maciej (Studia Oeconomica Posnaniensia, 2016)
Author presents the concept of an abusive clause as a contractual term which has not been individually negotiated with a consumer - contrary to a requirement of good faith - which determines rights and obligations arising under the contract and grossly violates a consumer’s interests. The main essence of the article is to introduce the impact of these clauses on a level of legal risk. The main aim is to provide an answer to the question: how to avoid or reduce legal risks associated with the negative legal effects of including abusive clauses in an agreement? The answer to this question is to provide appropriate action that can be used by entrepreneurs to avoid including an agreement abusive clauses, or, in a case where such provisions are already included, minimize the negative effects of their legal consequences. The considerations are carried out from the perspective of an entrepreneur, for whom special privilege for the consumer may pose a threat of adverse legal consequences, having impact on his or her legal and financial situation.